PENGARUH PERCEIVED QUALITY, INOVASI, KELOMPOK REFERENSI, DAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN SEPATU SEPAK BOLA MEREK NIKE - Galih Sartono; Retno Susanti; Lamidi Lamidi (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2019)
The purpose of this study was to analyze the significance of the effect of perceived quality, product innovation, reference groups, celebrity endorsers on purchasing decisions and knowing the independent variables that has a dominant effect on the purchase decision of soccer shoes brand Nike. This research is a census of the Football Boots Indonesia Regional Solo, totaling 52 people and all of them are used as research samples with population research or census techniques. This type of data use qualitative data and quantitative data. Data sources use primary data and secondary data. Data collection techniques use questionnaires, observation and literature study. Data analysis use multiple linear regression analysis. Perceived quality, reference groups and celebrity endorsers has a significant effect on the purchase decision of soccer shoes brand Nike on members of Football Boots Indonesia Regional Solo while product innovations have no significant effect on purchase decision soccer shoes brand Nike on members of Football Boots Indonesia Regional Solo.Keywords: perceived quality, product innovation, reference group, celebrity endorser, purchasing decision